AMMONIATION OF RICE STRAW AND SUPPLEMENTATION OF Paraserianthes falcataria AND Sapindus rarak ON IN VITRO RUMEN FERMENTATION AND METHANE PRODUCTION - Anuraga Jayanegara; Nanang Krisnawan; Yeni Widyawati; Asep Sudarman (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This study aimed to observe the effects of rice straw ammoniation and supplementation of Paraserianthes falcataria and Sapindus rarak on rumen fermentation and methane production in vitro. Rice straw was ammoniated by adding 2% urea. Rice straw, ammoniated rice straw, P. falcataria leaves and S. rarak fruits were oven-dried and finely ground. Experimental treatments were arranged as follow: rice straw (T1), ammoniated rice straw (T2), T2 80% + P. falcataria 20% (T3), T2 60% + P. falcataria 40% (T4), T2 80% + P. falcataria 10% + S. rarak 10% (T5), and T2 60% + P. falcataria 20% + S. rarak 20% (T6). An amount of 1 g sample from each treatment was added with 100 ml rumen fluid and buffer mixture (1:2 v/v), and incubated in a water bath at 39 ºC for 48 h. The incubation was performed in four replicates and each replicate was represented by four incubation bottles. Results showed that urea treatment increased gas production of rice straw at 24 and 48 h, higher ammonia production, higher IVDMD, and lower methane production as compared to the untreated rice straw (P<0.05). Addition of P. falcataria or S. rarak at lower level produced similar ammonia concentration as ammoniated rice straw whereas their addition at higher level decreased ammonia concentration (P<0.05). Paraserianthes falcataria addition to ammoniated rice straw decreased protozoa population (P<0.05) and S. rarak further decreased the fauna population (P<0.05) as well. Inclusion of S. rarak at 20% DM (T6) produced the lowest methane production both at 24 and 48 h after incubation and lowest methane production per unit of DM degraded. It was concluded that ammoniation of rice straw improved its nutritional quality with lower methane production, and its mixture with P. falcataria and S. rarak further increased the quality and lower the production of methane, respectively.